Avaliação do potencial neuroprotetor da Spirulina platensis em modelo de hemorragia intracerebral experimental - Almeida, Timóteo Abrantes de Lacerda (2016)
Intracerebral hemorrhage cases illustrate one of the diseases with high incidence, high mortality, and the ability to result in loss of human dignity, with a large number of survivors living with severe disabilities. The elderly population is especially susceptible to suffering by the loss of autonomy after an acute illness since the acute event aggregates to other biological and cultural factors of aging. With aging of the population, it is likely that the number of patients with noninfectious chronic diseases, including spontaneous cerebral hemorrhage, will rise. This is a complex public health problem, not only by its high incidence but due to the high associated mortality and the high incidence of severe disability among survivors. We have evaluated the effect of the pretreatment with Spirulina platensis for a period of 30 days in a rat model of cerebral hemorrhage. We hypothesized that Spirulina platensis and its major protein component, phycocyanin C, could mitigate the secondary cellular injury in the perilesional zone, through its antioxidant, anti-inflammatory and iron chelator activity, by interacting with cellular mechanisms of neuronal death. Experimental studies are required to prove its potential neuroprotective effect, as well as to determine the optimum period of treatment and appropriate dose